Growth and Poverty in Burkina Faso: A Reassessment of the Paradox - Michael Grimm; Isabel Günther (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
Previous poverty assessments for Burkina Faso were due to the neglect of some important methodological issues misleading and led to the so-called ?Burkinab? Growth-Poverty-Paradox?, i.e. relatively sustained macro-economic growth, but almost constant poverty. We estimate that poverty significantly decreased between 1994 and 2003 at least on the national level, i.e. growth was in contrast to what previous poverty estimates suggested ?pro-poor?. However, we also demonstrate that between 1994 and 1998 poverty indeed increased despite a good macroeconomic performance. This was due to a severe drought and a resulting profound deterioration of the purchasing power of the poor; an issue which was also overseen by previous studies.
Keywords: O12; I32; D63; D12; 330; Poverty; Pro-poor Growth; Differential Inflation; Sub-Saharan Africa; Burkina Faso